Differentially Private Group-by Data Releasing Algorithm - Chaves, Iago; Machado, Javam (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2019: Anais do XXXIV Simpósio Brasileiro de Banco de Dados, 2019)
Privacy concerns are growing fast because of data protection regulations around the world. Many works have built private algorithms avoiding sensitive information leakage through data publication. Differential privacy, based on formal definitions, is a strong guarantee for individual privacy and the cutting edge for designing private algorithms. This work proposes a differentially private group-by algorithm for data publication under the exponential mechanism. Our method publishes data groups according to a specified attribute while maintaining the desired privacy level and trustworthy utility results.